PENGUATAN OLAHRAGA PENCAK SILAT SEBAGAI WARISAN BUDAYA NUSANTARA - muhammad muhyi; Purbojati purbojati (Universitas PGRI Adi Buana Surabaya, 2014)
Sports martial arts (pencak silat) has grown and developed over the establishment of the Indonesian nation, even before Indonesia’s independence. It needs to be strengthened in order to continue to grow stronger in Indonesia. In order to realize it, the pillars of the national culture must be upheld which includes (1) construction of identity and character of the nation (2) Preservation of cultural heritage (3) development work / innovation and cultural diplomacy (4) institutional and human culture, and (5) facilities and infrastructure culture. To strengthen the construction of the five pillars of culture-related sports martial arts, the various concrete support pillars can help in any martial arts in the cultural heritage of the archipelago of Indonesia as well maintained. Keywords: sports martia arts, national culture, culural heritage.